Genome comparison of two Exiguobacterium strains from high altitude andean lakes with different arsenic resistance: identification and 3D modeling of the Acr3 efflux pump - Ordoñez, Omar F.; Lanzarotti, Esteban O.; Kurth, Daniel G.; Cortez, Néstor; Farias, Maria E.; Turjanski, Adrian G. (Frontiers in Environmental Science, 2015)
Arsenic exists in natural systems in a variety of chemical forms, including inorganic arsenite (As [III]) and arsenate (As [V]). The majority of living organisms have evolved various mechanisms to avoid occurrence of arsenic inside the cell due to its toxicity. Common core genes include a transcriptional repressor ArsR, an arsenate reductase ArsC, and arsenite efflux pumps ArsB and Acr3. To understand arsenic resistance we have performed arsenic tolerance studies, genomic and bioinformatic analysis of two Exiguobacterium strains, S17 and N139, from the high-altitude Andean Lakes. In these environments high concentrations of arsenic were described in the water due to a natural geochemical phenomenon, therefore, these strains represent an attractive model system for the study of environmental stress and can be readily cultivated. Our experiments show that S17 has a greater tolerance to arsenite (10nM) than N139, but similar growth in arsenate (150nM). We sequenced the genome of the two Exiguobacterium and identified an acr3 gene in S17 as the only difference between both species regarding known arsenic resistance genes. To further understand the Acr3 we modeled the 3D structure and identified the location of relevant residues of this protein. Our model is in agreement with previous experiments and allowed us to identify a region where a relevant cysteine lies. This Acr3 membrane efflux pump, present only in S17, may explain its increased tolerance to As(III) and is the first Acr3-family protein described in Exiguobacterium genus.